Hubungan antara Self-Esteem dengan Body Dissatisfaction pada Mahasiswi Psikologi Universitas Negeri Surabaya - Nur Aviatur Rohmatin; Mimbar Oktaviana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aim to examined the relationship between self-esteem and body dissatisfaction among females psychology students at Surabaya State University. Body dissatisfaction is a psychological phenomenon experienced by individuals and is widespread as a result of the internalization of influences from the surrounding environment. Self-esteem serves as a comprehensive process of self-evaluation or self-assessment. A quantitative approach using a corelational design was employe in this study, which included 425 female students as research subjects selected through purposive sampling. Data collection was conducted by administering a questionnaire designed to measure self-esteem and body dissatisfaction. The data were analyz use Pearson corelation test. The findings of this study indicated that there is a significants relationship between self-esteem and body dissatisfaction, with a value of r=0.403 and a significance value of <0.001, which is <0.05. This study offers a unique contribution as a foundation for the developments of literature on self-esteem and body dissatisfaction, demonstrating that the relationship between these two variables has different directions depending on how female college students construct their self-evaluations.